PENINGKATAN PENGETAHUAN IBU HAMIL TENTANG PEMENUHAN GIZI SELAMA KEHAMILAN DALAM RANGKA PENCEGAHAN KASUS STUNTING - Fildza Alya Iqlima; Ika Sumiyarsi Sukamto; Emalia Rizqi Anggita; Zulfa Nadia; Desy Vidi Kurniasari; Nailah Khairunnisa (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
Stunting remains a chronic nutritional issue and a major public health concern, including in Klaten Regency, Central Java. Klaten Tengah District has a high stunting prevalence, partly due to limited nutritional knowledge among pregnant women. This community engagement aimed to enhance their understanding of pregnancy nutrition through multimedia-based education. A descriptive quantitative method with a pretest-posttest design was applied to 20 pregnant women at Klaten Tengah Public Health Center. The intervention involved an educational video and discussion session. Wilcoxon Signed-Rank Test showed a significant increase in knowledge scores from 78 to 98 (p = 0.0002). The results indicate that multimedia education effectively improves pregnant women’s knowledge of nutritional needs, supporting its use as a community-level strategy to prevent stunting.